Molecular epidemiological study of animal rabies in Kazakhstan - Gulzhan N. YESSEMBEKOVA; Shuang XIAO; Assem ABENOV; Talgat KARIBAEV; Alexandr SHEVTSOV; Amirgazin ASYLULAN; Yersyn Y. MUKHANBETKALIYEV; Lei SHUAI; Zhi-gao BU; Sarsenbay K. ABDRAKHMANOV (Journal of Integrative Agriculture, 2023)
Rabies is a serious public health issue in Kazakhstan, with high economic impact and social burden. As part of a routine surveillance, 31 rabies-positive brain specimens taken from livestock (cattle) and carnivores (dogs, foxes, and cats) during 2013–2021 were subject to viral sequencing. Phylogenetic and Bayesian analysis were performed using obtained rabies virus (RABV) sequences. All 31 strains of RABV candidate belonged to the Cosmopolitan clade, of which 30 strains belonged to steppe-type subclade, and 1 dog strain belonged to Other subclade. The 31 strains did not diverge from RABV strains in Kazakhstan and neighboring countries, including Russia, Mongolia, and China, suggesting that animal rabies has close relationship and transmission between borders. Fox-originated strains and cattle strains shared similar sequence signature, and some animal rabies cases had space–time intersection, showing that infected foxes were a major transmission source of cattle rabies in different Kazakhstan regions. Besides, free-roaming dogs played a pivotal role in rabies epizootics of cattle in Kazakhstan. The recent spread of animal rabies presents an increasing threat to public health, and provides updated information for improving current control and prevention strategies at the source for Kazakhstan and neighboring countries.